2012
DOI: 10.1016/j.jaerosci.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diffusion charging and mobility-based methods for measurement of aerosol agglomerate surface area

Abstract: We compare different approaches to measure surface area of aerosol agglomerates. The objective was to compare field methods, such as mobility and diffusion charging based approaches, with laboratory approach, such as Brunauer, Emmett, Teller (BET) method used for bulk powder samples. To allow intercomparison of various surface area measurements, we defined 'geometric surface area' of agglomerates (assuming agglomerates are made up of ideal spheres), and compared various surface area measurements to the geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The assumption is that all the primary particles are equally exposed to the surrounding gas: the aggregates need to be linear-chain assumption with a low fractal dimension. Recently, Ku and Kulkarni (2012) showed that the geometric surface area of aggregates is underestimated by the IA method applied to mobility analysis when the chains have a fractal dimension of 2.37-2.63. Because no statistical morphology analysis was carried out in this study, the SMPS surface area can be considered only an estimation of geometric surface area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption is that all the primary particles are equally exposed to the surrounding gas: the aggregates need to be linear-chain assumption with a low fractal dimension. Recently, Ku and Kulkarni (2012) showed that the geometric surface area of aggregates is underestimated by the IA method applied to mobility analysis when the chains have a fractal dimension of 2.37-2.63. Because no statistical morphology analysis was carried out in this study, the SMPS surface area can be considered only an estimation of geometric surface area.…”
Section: Discussionmentioning
confidence: 99%
“…The size distribution measurement, and thus the estimated surface area, is affected by the morphology and aggregation of the particles (Lall and Friedlander 2006) but these are typically not known with precision in occupational environments without in-depth analysis. Studies that compared the results of these methods for measuring the surface area of ultrafine and nanoaerosols have been performed (Ku 2010) and recently concluded (Ku and Kulkarni 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although methods that measure surface area on-line are available (Asbach, Fissan, Stahlmecke, Kuhlbusch, & Pui, 2009;Fierz, Houle, Steigmeier, & Burtscher, 2011;Ntziachristos, Giechaskiel, Ristimäki, & Keskinen, 2004;Wang et al, 2010), these were typically not developed for non-spherical and porous particles, and thus do not work in an optimal way for all types of aggregates (LeBouf et al, 2011). Also there is data suggesting that the techniques based on unipolar diffusion charging does not relate directly to the surface area of the aerosol particles as suggested (Gopalakrishnan, Thajudeen, Ouyang, & Hogan, 2013;Ku & Kulkarni, 2012;Ku & Maynard, 2005). Transmission electron microscopy (TEM) imagery is often used to characterize primary particle size (d pp ) of aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used for specific surface area characterization, whereof nitrogen adsorption, or Brunauer Emmett Teller (BET) is the most common (Brunauer, Emmett, & Teller, 1938). BET has been successfully used for nanoparticle surface area characterization (Eggersdorfer, Groehn, Sorensen, McMurry, & Pratsinis, 2012;Ku & Kulkarni, 2012). However, the technique can prove challenging for many applications and nanoparticle sources since it is offline and a relatively large amount of material is needed (min.…”
Section: Introductionmentioning
confidence: 99%
“…Ehara et al, 1996) tandem DMA/APM (e.g. Mc Murry et al, 2002;Ku et al, 2006;Pagels et al, 2009;Kim et al, 2009;Ku and Kulkarni, 2012;Shapiro et al, 2012;Rissler et al, 2013;Charvet et al, 2014). Measured particle diameter and mass are basic parameters which should simplify data collection and interpretation.…”
Section: Introductionmentioning
confidence: 99%